The Role of Zakat in Poverty Alleviation: A Comprehensive Review of Economic Impact Assessments - Saputra, Andika; Sutopo, Heri (Economics Studies and Banking Journal (DEMAND), 2024)
Zakat, as an obligation in Islam, has significant potential in alleviating poverty and economic empowerment. This research aims to evaluate the effectiveness of various types of zakat in reducing poverty through a comprehensive literature review. The method used is the PRISMA approach to ensure systematization and transparency in literature collection and screening. The research results show that zakat fitrah, zakat mal, and zakat profession play an important role in reducing poverty and improving community welfare. The implications of this research highlight the importance of good, transparent zakat management and the use of digital technology to increase the efficiency of zakat collection and distribution. This research also identifies the need for more in-depth empirical studies and the use of more effective distribution strategies in the context of poverty alleviation.